2007
DOI: 10.1016/j.bone.2007.04.195
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate preserves bone mass for at least 2 years following acute administration for pediatric burn injury

Abstract: We have previously shown that pamidronate, when given within ten days of burn injury, preserves lumbar spine bone mineral content from admission to discharge in 6-8 weeks and at six months increases both lumbar spine and total body bone mineral content (BMC) over placebo. We followed patients unblinded after 6 months every 3 months up to 2 years post-burn to see if the effects of pamidronate were sustained. Additionally, we assessed bone remodeling at one year post-burn by iliac crest bone biopsy. We enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Oxandrolone is the most studied anabolic drug in burn patients, is safe and has demonstrated beneficial effects in lean mass restoration [39,40]. Antiresorptive agents such as bisphosphonates have been studied in burn children with promising result both on bone [41,42] and muscle mass [43]. Place of bone anabolic drugs (such as strontium ralenate or anti-sclerostin antibody) has to be specified in burn related bone loss management.…”
Section: Normal Rangesmentioning
confidence: 98%
“…Oxandrolone is the most studied anabolic drug in burn patients, is safe and has demonstrated beneficial effects in lean mass restoration [39,40]. Antiresorptive agents such as bisphosphonates have been studied in burn children with promising result both on bone [41,42] and muscle mass [43]. Place of bone anabolic drugs (such as strontium ralenate or anti-sclerostin antibody) has to be specified in burn related bone loss management.…”
Section: Normal Rangesmentioning
confidence: 98%
“…These early resorptive changes would explain the efficacy of acute intravenous administration of bisphosphonates in prevention of bone loss in children following burn injury [2, 5]. In addition, a study in adults within the first week following burns by Leblebici et al [9] demonstrated an elevation of urinary deoxypyridinoline excretion, also consistent with early increased resorption.…”
Section: Discussionmentioning
confidence: 99%
“…By 2 weeks post-burn patients already have adynamic bone as evidenced by markedly reduced bone formation [35], reduced urinary markers of bone resorption [4], and reduced osteoblast differentiation [6]. However, if bisphosphonates are given intravenously within the first 10 days of the burn injury, the bone loss is entirely blocked [2, 5]. Therefore, it is possible that the acute bone loss could be the result of bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…By two weeks after the burn injury in children there are virtually no surface osteoblasts seen on iliac crest bone biopsy [3,7]. Study of glucocorticoid receptor messenger RNA (mRNA) in bone tissue by real time polymerase chain reaction (RTPCR) showed a trend toward reduction of the glucocorticoid receptor mRNA and a significant reduction of type I collagen mRNA in iliac crest bone biopsies of burned patients compared to controls [4].…”
Section: Overview Of Pertinent Pathophysiologic Responses To Burnsmentioning
confidence: 97%
“…Having provided evidence for progressive vitamin D deficiency following burn injury, we must place this in the context of resolving bone problems by one year post-burn, including the resumption of bone remodeling [7] and the resolution of hypocalcemia and hypoparathyroidism. Thus the progressive vitamin D deficiency post-burn may be responsible for failure of bone mass to return to a more normal range [24].…”
Section: The Natural History Of Vitamin D Me-tabolism Post-burnmentioning
confidence: 98%